Improvement in the California bearing ratio of subbase soil by recycled asphalt pavement and cement - Al-Fatlawy Rasha A.; Ali Tawfek Sheer; Fakhraldin Mohammed K.; Hussain Nibras A.; Abd Ibtihal Y. (Open Engineering, 2023)
As the subbase layer is one of the important layers in road construction, it is necessary to use a granular material to resist traffic loads. Usually, granular soil with a good gradation is used, which is determined by most road design codes. Sometimes it is needed to improve the properties of this soil by adding materials such as cement, which is considered a high-cost material, so it is necessary to search for low-cost materials. One of these materials is recycled asphalt pavement (RAP). Herein, we presented an experimental study to investigate using RAP and cement in roadway subbase material improvement. The indicator of the improvement has been selected as the California bearing ratio (CBR); many laboratory tests were made for many percentages of cement and RAP. The study’s main conclusions are that the CBR value increases when the cement percentage increases and the RAP percentages increase up to 12% by the mass of the virgin subbase and then decrease. Also, using a mix of 12% RAP and 1% cement blended with the subbase material gives a CBR value of 138.6. This improvement is considered the same as using 6% (133.5) cement but it is of low cost due to the low cost of the waste material (RAP) as it saved the high cost of 5% cement.